2020
DOI: 10.1016/j.numecd.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships among common predictors of cardiovascular diseases in patients of OSA: A large-scale observational study

Abstract: Background and aims: The apolipoprotein B/apolipoprotein A-I (ApoB/ApoA-I) and insulin resistance has been recognized as common cardiovascular diseases (CVD) risk factors. However, whether they were biomarkers for 10-year CVD risk in obstructive sleep apnea (OSA) had been rarely studied. Besides, interrelationships between the ApoB/ApoA-I, insulin resistance and OSA remain unclear. Methods and results: A total of 4010 subjects were finally included. Anthropometric, fasting biochemical, and polysomnographic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
6
2
Order By: Relevance
“…In this study, we demonstrated that 59.6% of apnoeic individuals had a moderate-to-high 10-year CVD risk, which is significantly higher than in the general population [ 41 ]. However, the rate of apnoeic individuals with moderate-to-high 10-year CVD risk highlighted in our study seems to be higher than that of the study by Li et al (2020) [ 42 ]. Indeed, in this previous study, only 34.0% of apnoeic individuals had a moderate-to-high 10-year CVD risk [ 42 ].…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…In this study, we demonstrated that 59.6% of apnoeic individuals had a moderate-to-high 10-year CVD risk, which is significantly higher than in the general population [ 41 ]. However, the rate of apnoeic individuals with moderate-to-high 10-year CVD risk highlighted in our study seems to be higher than that of the study by Li et al (2020) [ 42 ]. Indeed, in this previous study, only 34.0% of apnoeic individuals had a moderate-to-high 10-year CVD risk [ 42 ].…”
Section: Discussioncontrasting
confidence: 94%
“…However, the rate of apnoeic individuals with moderate-to-high 10-year CVD risk highlighted in our study seems to be higher than that of the study by Li et al (2020) [ 42 ]. Indeed, in this previous study, only 34.0% of apnoeic individuals had a moderate-to-high 10-year CVD risk [ 42 ]. However, compared to our study, the apnoeic individuals recruited in the study by Li et al (2020) had a better demographic (younger age and lower body mass index) and cardiometabolic profile (lower prevalence of type 2 diabetes, hypertension, and dyslipidaemia) [ 42 ], which may have led to an underestimation of the 10-year CVD risk in their study given the major role played by these demographic and cardiometabolic factors in the development of CVD [ 28 ].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Moreover, OSA is strongly associated with metabolic disorders such as obesity, hypertension, dyslipidemia, and glucose metabolic diseases. Therefore, this disease can be considered as a key risk factor for CVD (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that differences exist in the reasons for ED visit between patients with OSA and without OSA, especially with respect to Respiratory, Cardiovascular and Lymphatic categories. According to the research of May AM [18] and Li X [19], there are strong associations betwen OSA and cardiac arrhythmias and cardiovascular disease. On the other hand, through the research of Owens RL [20], we can learn that there is a reciprocal interaction between chronic obstructive pulmonary disease and OSA.…”
Section: Discussionmentioning
confidence: 99%